2022
DOI: 10.1021/acs.biochem.1c00780
|View full text |Cite
|
Sign up to set email alerts
|

A Difference between In Vitro and In-Cell Protein Dimer Formation

Abstract: The high concentration of macromolecules in cells affects the stability of proteins and protein complexes via hard repulsions and chemical interactions, yet few studies have focused on chemical interactions. We characterized the domain-swapped dimer of the B1 domain of protein G in buffer and Escherichia coli cells by using heteronuclear, multidimensional nuclear magnetic resonance spectroscopy. In buffer, the monomer is a partially folded molten globule, but that species is not observed in cells. Experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These discrepancies between the highly crowded cellular environment and dilute protein solutions that are used in most experiments can result in different protein behavior (Speer et al, 2022). Specifically, species observed in buffer are not necessarily observed in cells (Chu et al, 2022; Cohen & Pielak, 2017) and disordered proteins can exhibit different ensembles in cells than they do in buffer (Dedmon et al, 2002). Surprisingly, how crowding impacts protein folding and folded state stability in concentrated environments is yet to be fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies between the highly crowded cellular environment and dilute protein solutions that are used in most experiments can result in different protein behavior (Speer et al, 2022). Specifically, species observed in buffer are not necessarily observed in cells (Chu et al, 2022; Cohen & Pielak, 2017) and disordered proteins can exhibit different ensembles in cells than they do in buffer (Dedmon et al, 2002). Surprisingly, how crowding impacts protein folding and folded state stability in concentrated environments is yet to be fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…All biological functions are driven by interactions. The protein interactions with cellular environment have been shown to affect protein conformation (9,23,(27)(28)(29), folding and stability (11,12,14,16,40), and proteinprotein binding (18,(20)(21)(22) in cells. Here, we showed that the interactions also affect protein loop dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The interior of a cell is crowded with ions, metabolites, and macromolecules. Through excluded volume effect (1) or direct weak interactions (such as electrostatics, H-bonding, and stacking), which drive proteins to form quinary structures (2)(3)(4)(5), the cellular environment can change protein diffusion (6)(7)(8)(9), protein folding (10)(11)(12)(13)(14)(15)(16)(17), and protein ligand binding (18)(19)(20)(21)(22)(23)(24). For intrinsically disordered proteins (IDPs), the excluded volume effect limits their conformational space so that they tend to adopt more compact conformations (9,25).…”
Section: Introductionmentioning
confidence: 99%
“…15 On the other hand, the reaction of the GB1 domain-swapped dimer 16,17 changes from an equilibrium between a folded dimer and a molten globule monomer in buffer to one between the dimer and unfolded monomers in Escherichia coli cells, suggesting that attractive chemical interactions in cells unfold the protein. 18 Although not directly physiologically relevant, the crowding effects of synthetic polymers are essential to the pharmaceutical and chemical industries where they are used as excipients to protect biological drugs, vaccines, and commercial enzymes. 19−21 Polyethylene glycols (PEGs), which are used to formulate pharmaceutically and industrially important proteins and vaccines, 21 are the most commonly employed synthetic polymers for crowding experiments because of their high solubility, low polydispersity, and availability in a range of molecular weights.…”
mentioning
confidence: 99%
“…For example, the stability of the side-by-side dimer made from the B1 domain of protein G (GB1) increases in both prokaryotic and eukaryotic cells compared to buffer, probably because of repulsive chemical interactions between the GB1 monomer and intracellular macromolecules . On the other hand, the reaction of the GB1 domain-swapped dimer , changes from an equilibrium between a folded dimer and a molten globule monomer in buffer to one between the dimer and unfolded monomers in Escherichia coli cells, suggesting that attractive chemical interactions in cells unfold the protein …”
mentioning
confidence: 99%